2003
DOI: 10.3748/wjg.v9.i5.1034
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor expression in the basolateral nucleus of amygdala of conditioned taste aversion rats

Abstract: AIM: To determine whether serum leptin level and the leptin receptor (OB-R) expression in the basolateral amygdala (BLA) change following conditioned taste aversion (CTA) formation. METHODS:The serum leptin concentration was measured by rat leptin RIA kit, long and short forms of leptin receptor (OB-Rb and OB-Ra) mRNA in the brain sections were examined by in situ hybridization (ISH) and the expression of OB-R was assessed by immunohistochemistry ABC method with a highly specific goat anti-OB-R antibody. RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Leptin receptors are located in the basolateral amygdala (BLA) (Han et al, 2003), but their impact on behaviors outside of feeding—such as emotion, learning, and behaviors such as fear, aggression, and addiction—remain unclear. In a congenital leptin deficient patient, leptin treatment decreased activation of the amygdala in response to pictures of food (Frank et al, 2011).…”
Section: Leptin’s Role In Psychopathologymentioning
confidence: 99%
“…Leptin receptors are located in the basolateral amygdala (BLA) (Han et al, 2003), but their impact on behaviors outside of feeding—such as emotion, learning, and behaviors such as fear, aggression, and addiction—remain unclear. In a congenital leptin deficient patient, leptin treatment decreased activation of the amygdala in response to pictures of food (Frank et al, 2011).…”
Section: Leptin’s Role In Psychopathologymentioning
confidence: 99%
“…serotonergic raphe nuclei [31] and anxiety behavior, e.g. amygdala were reported to express leptin receptors [32]. In addition, the hippocampus, an anatomical site that governs cognitive functions and spatial learning, express LRb receptor isoform.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that dysregulation of leptin may be related to mechanisms of psychopathology, including various emotional changes, such as anxiety, depression, sleep disorders, and suicide [18,19]. In addition, the leptin receptors and their projections in the amygdala, which is a major structure for anxiety and stress-related emotional changes, offer another basis for the association with emotional changes [20]. Females, compared to males, show increased levels of morning plasma leptin after sleep restriction [21].…”
Section: Discussionmentioning
confidence: 99%